Pseudopygmephorellus mazandaranicus sp. nov. (Acari: Heterostigmata: Pygmephoridae), phoretic on scarabaeid dung beetles (Coleoptera: Scarabaeidae) from Iran - Katlav, Alihan; Hajiqanbar, Hamidreza; Talebi, Ali Asghar (Zootaxa, 2015)
The mite species Pseudopygmephorellus mazandaranicus Katlav and Hajiqanbar sp. nov. (Acari: Prostigmata: Pygmephoridae) is described and illustrated from northern Iran. This new species was discovered phoretic on three different scarabaeid dung beetles: Onthophagus sp., Aphodius depressus (Kugelann, 1792), Aphodius varians Duftschmid, 1805. This finding presents the first record of the genus Pseudopygmephorellus Khaustov, 2008 from Asia. The host range/habitat and world-wide distribution of species of the genus Pseudopygmephorellus is reviewed and a key to world species of the genus is provided.